Anti-Inflammatory, Antioxidant, and Microbiota-Modulating Effects of Camellia Oil from Camellia brevistyla on Acetic Acid-Induced Colitis in Rats - Chun-Ching Wu; Yu-Tang Tung; Sheng-Yi Chen; Wei-Ting Lee; Hsin-Tang Lin; Gow-Chin Yen (MDPI AG, 2020)
Altering the microbiota by the daily diet is highly associated with improved human health. Studies confirms the gastrointestinal protective and anti-inflammatory effects of camellia oil; however, the benefits in gut microbiota remain unclear. Camellia oils of Camellia oleifera (PCO) and C. brevistyla (TCCO) were used to evaluate probiotic growth in vitro. In addition, the protective effects of camellia oils in the acetic acid (AA)-induced colitis rat model were investigated. In vitro fermentation study showed the proliferation of Lactobacillus spp. and Bifidobacterium spp. from human intestinal microbiota was increased after TCCO treatment. Moreover, the rats pretreated with TCCO exhibited significantly less AA-induced colonic injury and hemorrhage, higher serum immunoglobulin G 1 (IgG 1) levels, lower malondialdehyde levels, and lower inflammatory cytokine production in the colon tissue compared with those in the PCO group. Surprising, the protective effect against acetic acid-induced colitis by TCCO was similar to sulfasalazine (positive control) treatment. Moreover, TCCO increased the richness and diversity of probiotics in gut microbiota. TCCO alleviated AA-induced colitis by modulating gut microbiota, reducing oxidative stress and suppressing inflammatory responses.